Author Correction: Imidazole propionate is increased in diabetes and associated with dietary patterns and altered microbial ecology - Antonio Molinaro (Nature Portfolio, 2020)
A Correction to this paper has been published: https://doi.org/10.1038/s41467-020-20412-9.